Case Report: Community-Acquired Legionella gormanii Pneumonia in an Immunocompetent Patient Detected by Metagenomic Next-Generation Sequencing - Lei, Cheng; Zhou, Xianglin; Ding, Shuizi; Xu, Yingjie; Yang, Binyi; Guo, Wei; Song, Min; Yang, Min; Jia, Yunan; Luo, Hong (Frontiers in Medicine, 2022)
Background: Legionella spp. has been well recognized as an important cause of community-acquired pneumonia. Current community-acquired pneumonia guidelines recommended cover the treatment of Legionella because of the high mortality associated with inadequate antibiotic treatments. However, the symptom of Legionella pneumonia is non-specific, and routine diagnostic tests exhibit low sensitivity for Legionella spp., especially for non-Legionella pneumophila serogroup 1 strains. Case presentation: We report a 53-year-old man without underlying diseases admitted to respiratory intensive care unit because of severe community-acquired pneumonia and respiratory failure. Although the results of routine culture of bronchoalveolar lavage fluid and the Legionella urinary antigen test were all negative, metagenomic next-generation sequencing (mNGS) identified a great amount of DNA and RNA sequences of Legionella gormanii in bronchoalveolar lavage fluid while negative in blood sample. The presence of Legionella gormanii in bronchoalveolar lavage fluid was further confirmed by polymerase-chain-reaction and Sanger sequencing. Conclusion: Legionella gormanii has rarely been reported in patients with community-acquired pneumonia mainly due to lack of diagnostic test for non-Legionella pneumophila serogroup 1 strains. This is the first report of Legionella gormanii pneumonia in an immunocompetent patient detected by mNGS, which indicated that mNGS is a high-resolution and sensitive assay for the diagnosis and surveillance of Legionella infection.